2018
DOI: 10.2147/copd.s146870
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the default mode network and cognitive impairments in patients with chronic obstructive pulmonary disease

Abstract: Background and objectivesCognitive impairment is a common extrapulmonary comorbidity in COPD patients. The default mode network (DMN) plays a critical role in maintaining the normal activities of humans, and its function can be evaluated by resting state functional magnetic resonance imaging. The aim of this study was to investigate the correlations between cognition and function changes of the DMN in COPD patients.MethodsOne hundred and thirteen eligible participants including 30 control subjects and 83 COPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Structural MRI studies found decreased GM in the dorsolateral PFC [ 11 ], and this part of the brain is involved in executive functions and working memory [ 12 ]. Resting-state fMRI showed that patients with COPD have lower functional connectivity values in the cingulate cortex and PFC [ 34 ]. PFC plays an essential role in executive function, which is considered the higher cognitive function that would be more often affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural MRI studies found decreased GM in the dorsolateral PFC [ 11 ], and this part of the brain is involved in executive functions and working memory [ 12 ]. Resting-state fMRI showed that patients with COPD have lower functional connectivity values in the cingulate cortex and PFC [ 34 ]. PFC plays an essential role in executive function, which is considered the higher cognitive function that would be more often affected.…”
Section: Discussionmentioning
confidence: 99%
“…* * P ≤ 0:01; * * * P ≤ 0:001. [34]. PFC plays an essential role in executive function, which is considered the higher cognitive function that would be more often affected.…”
mentioning
confidence: 99%
“…One study found increased resting-state network activity in patients with COPD compared to healthy controls, but this result was not significant anymore after controlling for oxygen saturation [14]. Another study also found increased default network activation in patients with moderate COPD but decreased activation in those with severe COPD [44]. This result might reflect a compensatory response to damage inflicted by factors associated with COPD, and this response might be strongest in patients with moderate COPD [44].…”
Section: Longitudinal Studiesmentioning
confidence: 99%
“…Hu et al found that the MMSE score is inversely correlated with the severity of airflow obstruction. 28 However, Dag and Thakur examined cognitive function among stable COPD patients with the MoCA or MMSE, and they did not find any associations between COPD severity measures and the risk of cognitive impairment. 16 , 27 The study conducted by Salik et al showed that cognitive function in COPD patients with mild hypoxemia was similar to that observed for healthy subjects, and no relationship existed between MMSE scores and lung function parameters in either COPD or healthy subjects.…”
Section: Discussionmentioning
confidence: 98%